Knowledge and quality of life among Indonesian students during the COVID-19 pandemic - Prasojo Pribadi; Lolita Lolita; Rayi Citra Ayu Pangestuti; Heni Lutfiyati; Silvia Mareti; Azis Ikhsanudin (International Journal of Public Health Science (IJPHS), 2021)
The increasing of online coronavirus disease-2019 (COVID-19) information-sharing in digital media can contribute to the emergence of misinformation in public. Much insufficient knowledge will confuse public understanding and affect their quality of life. The study purposed to assess the knowledge and its influence on Indonesian students' quality of life during the COVID-19 crisis. A cross-sectional study was conducted between October and December 2020 by distributing online questionnaires. The data analysis was run through the Spearman correlation method by using SPSS version 21.0. A total of 200 respondents aged over 17 years were recruited using a snowball sampling technique. Most study respondents had insufficient knowledge about COVID-19, 23% of them had moderate knowledge, and only 17.5% had high knowledge. They obtained primary sources of COVID-19 information from social media platforms. The results showed that health science students have a better understanding than social science students (ρ<0.001). The level of knowledge has a significant associated with psychological domain (ρ=0.020), environmental domain (ρ=0.046), and overall quality of life (ρ=0.047). Thus, the media control center is vital to encounter valid information in providing better knowledge and quality of life during a pandemic.